BRAF(V600E )mutations in malignant melanoma are associated with increased expressions of BAALC - Schrama, David (Medknow Publications, 2008)
BACHGROUND: Activating BRAF mutations are present in approximately 50% of melanomas. Although different downstream target genes of the most common mutant V600E have been identified, the contribution of activating BRAF mutations to malignant transformation needs further clarification. METHODS: Microarray gene analysis was performed for human melanoma cell lines harboring BRAF(V600E )mutations in comparison to cell lines without this mutation. RESULTS: This analysis revealed a more than two fold down-regulation of 43 and an increase of 39 gene products. BAALC (Brain and acute Leukaemia, cytoplasmatic) was most prominently regulated, since it was up-regulated in mutated cell lines by a mean of 11.45. Real time PCR analyses with RNA from melanoma cell lines (n = 30) confirmed the BRAF-activation dependent up-regulation of BAALC. CONCLUSION: BAALC, which has been associated with cell dedifferentiation and migration, may function as a downstream effector of activating BRAF mutations during melanomagenesis.